2022
DOI: 10.3390/cells11111725
|View full text |Cite
|
Sign up to set email alerts
|

Across Dimensions: Developing 2D and 3D Human iPSC-Based Models of Fragile X Syndrome

Abstract: Fragile X syndrome (FXS) is the most common inherited cause of intellectual disability and autism spectrum disorder. FXS is caused by a cytosine-guanine-guanine (CGG) trinucleotide repeat expansion in the untranslated region of the FMR1 gene leading to the functional loss of the gene’s protein product FMRP. Various animal models of FXS have provided substantial knowledge about the disorder. However, critical limitations exist in replicating the pathophysiological mechanisms. Human induced pluripotent stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 160 publications
0
4
0
Order By: Relevance
“…sAPPα, therefore, plays an important role in the initial step of neuronal induction for proper brain development. Here, we observed an excess of sAPPα release in FXS NPCs derived by iPSCs in both 2D and 3D cellular models, which may underlie some of the pathological FXS phenotypes observed in NPCs [46,86,96] and the long-lasting defects reported in the mature neurons [90].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…sAPPα, therefore, plays an important role in the initial step of neuronal induction for proper brain development. Here, we observed an excess of sAPPα release in FXS NPCs derived by iPSCs in both 2D and 3D cellular models, which may underlie some of the pathological FXS phenotypes observed in NPCs [46,86,96] and the long-lasting defects reported in the mature neurons [90].…”
Section: Discussionmentioning
confidence: 74%
“…The reprogramming and differentiation of patient-derived cells into neurons allows investigators to model/duplicate some of the cellular and molecular features of neurodevelopmental disorders [83][84][85]. Neurons and brain organoids derived from FXS iPSCs recapitulate several cellular pathological aspects reported in the murine model, such as deficits in neurite initiation and outgrowth, increased protein synthesis, neuronal hyperactivity, and deficits in action potential firing and spontaneous synaptic activity [46,[86][87][88][89][90][91][92][93][94][95][96]. Moreover, FXS NPCs showed increased proliferation and protein synthesis [46,86,89,96], and several studies demonstrated the involvement of sAPPα in the proliferation and differentiation of murine NPCs [97][98][99][100].…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts from patients DEB125 and DEB135 were derived from a fresh dermal punch biopsy. Minced pieces (∼1mm 3 ) of biopsies were cultured in DMEM (Gibco 12-430-062) with 10% fetal bovine serum (FBS; Hyclone SH30406.02 New Zealand sourced) and 1% Penicillin-Streptomycin (Fisher Scientific 15140163). Media was changed every 4 days and fibroblasts started to grow out from the tissue at day 4 and 8, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…iPS cells can be differentiated into not only individual cell types, but also organotypic cultures or organoids containing multiple key cell types that compose a tissue. However, such complex, multi-lineage manufacturing methods have not yet been developed at scale for clinical evaluation [3][4][5] . The iPS cell-based approach provides a solution for the two main limitations of current somatic cell and gene therapy strategies: (i) iPS cells can be grown to virtually unlimited numbers providing a solid foundation for tissue organoid production-scalability and (ii) defined gene editing recreates a wild type allele while avoiding retroviral insertional mutagenesis.…”
Section: Introductionmentioning
confidence: 99%